Monetary policy rules and the effective lower bound in the Euro area - Markus Haavio; Olli-Matti Laine (Bank of Finland, 2021)
We analyze the economic performance of dierent monetary policy strategies, or rules, in a low interest rate environment, using simulations with a DSGE model which has been estimated for the euro area. We study how often the eective lower bound of interest rates (ELB) is likely to bind, and how much forgone monetary policy accommodation this entails. Macroeconomic outcomes are measured by the mean levels and the volatility of output (gaps), unemployment and ináation. We present three sets of results. First, the macroeconomic costs of the ELB are likely to grow in a non-linear manner if the monetary policy space (the dierence between the normal, or average, level of nominal interest rates and the ELB) shrinks. Second, a point ináation target appears to outperform a target range. Third, the (relative) performance of low-for-long (L4L) monetary policy rules depends on the size of the monetary policy space. The L4L rules tend to perform well, if the monetary space is small, but if the space is larger these rules, while stabilizing ináation, may lead to more volatility in the real economy than áexible ináation targeting.
URN:NBN:fi:bof-202104081174
Keywords: E31; E32; E52; E58; 330; monetary policy rules; effective lower bound; euro area